In Silico Study of SARS-CoV-2 Vaccine Candidate: Spike Glycoprotein - Arif Nur Muhammad Ansori (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aimed to perform the analysis of toxicity prediction, allergenicity prediction, and in silico cloningof peptides originated from SARS-CoV-2 spike glycoprotein in the previous study. Allergenicity predictionemployed AllerPred to predict the non-allergen peptides and toxicity prediction performed using ToxinPred.Then, this study designed the in silico cloning of SARS-CoV-2 spike glycoprotein with pET-28a(+) usingSnapGene software. Therefore, this study successfully constructed the SARS-CoV-2 vaccine candidate viain silico method. Therefore, these data could be used to design a peptide-based vaccine against SARSCoV-2. However, the advanced study is recommended confirmation, such as in vitro and in vivo study